REGULATION OF A RIGHT TO A SALARY IN THE INTERNATIONAL LEGAL INSTRUMENTS OF ILO AND UN AND THEIR IMPLEMENTATION IN THE INTERNATIONAL LABOUR LEGISLATION IN THE REPUBLIC OF MACEDONIA - Majhosev, Darko A; Risteska, Ivana (Journal of process management and new technologies, 2017)
This paper deals with the salary as the most important legal institute, element and principle of the labour relations. Before we approach the analysis of the legal regime of the salary, we will define the term labour relations. This paper puts special emphasis on the terminology of the notion salary, as well as the legal nature of the legal regime of the salary. Additionally, in this paper the most important international legal instruments of ILO, UN and The European Council are analyzed for salary regulation and ban on compensation discrimination. In this context, the most important legal acts in the Republic of Macedonia are analyzed which regulate the legal institute salary, i.e. the minimum wage (The Constitution, Labour Law, and Law on Minimum Wage).